Penerimaan Sumber Daya Manusia Brigadir Polri dalam Perspektif Governance (Studi Penerimaan Sumber Daya Manusia Kepolisian Daerah Bali Tahun Anggaran 2015) - Austriani, Ni Luh Putu Vina; Erviantono, Tedi; Purnamaningsih, Eka (CITIZEN CHARTER, 2016)
ABSTRACT The acceptance about Human Resourcesof Police Brigadir an effort to find a qualified personnel police Brigadir in accordance with prescribed rules, but it always rising the problem in practical level. With the frequent occurrence of the problems at the practical level, researchers reviewing which is relating to the governance as measured by indicators of transparency and accountability. Polda Bali as local police located in the province of Bali which is carrying out of Brigadir implement revenue. In this research use descriptive qualitative method. To obtain the data, the authors did a field observationÂ  as well as in-depth interviews associated with the acceptance of human resources of Police Brigadir in Polda Bali fiscal year 2015. The result of this research are: First the implementation of Police Brigadir revenue in Polda Bali using principles BTAH (Clean, Transparent, Accountable, Humanist) which is used as a reference in the implementation. Second, before the test begins there are the creation of a treaty and signatories of a written or spoken commitment it called pakta intergritas. Third, looking from indicators of transparency in the implementation process of tests Police Brigadir revenue from the beginning to the end already fulfill the transparency but related to the socialization of SMA/SMK is not maximal yet. Fourth, as general looking from indicators of accountability for implementing Police Brigadir revenue has been good although there are differences in the phenomenon of measuring instruments used. This research is expected with the implementation of Police Brigadir revenue of accountability associated with the tool used is prepared. Keywords: Human Resources, Good Governance, Transparency and Accountability.